CDF-1 mediated repression of cell cycle genes targets a specific subset of transactivators. - Zwicker, J (1998)
The cdc25C, cyclin A and cdc2 genes are regulated during the cell cycle through two contiguous repressor binding sites, the CDE and CHR, located in the region of transcription initiation and interacting with a factor termed CDF-1. The target of this repression seems to be transcriptional activation of these promoters by transcription factors bound upstream. The majority of these factors falls into the class of glutamine-rich activators, suggesting that CDF-1-mediated repression might be activation domain specific. In the present study we have used chimeric promoter constructs to demonstrate that the cdc25C UAS, but not the core promoter, is crucial for repression. In addition, we show that only specific transcription factors and activation domains are responsive to CDE-CHR-mediated cell cycle regulation. These observations clearly indicate that CDF-1 interferes with activation of transcription by a specific subset of transactivators. The repressible activation domains belong to the same class of glutamine-rich activators, pointing to specific interactions of CDF-1 with components of the transcription machinery. In agreement with this conclusion we find that a simple inversion of the CDF-CHR module completely abrogates cell cycle-regulated repression.